The pious man and his sons: quran stories for little hearts - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
This story follows a devoted father who imparts valuable lessons of faith and morality to his sons. Through various challenges, he teaches them the importance of righteousness, kindness, and the consequences of their actions, inspiring young readers to embrace these virtues in their own lives.